(untitled) (Biological Sciences - PJSIR, 2008)
Combining abilities of cotton varieties were evaluated using a line x tester design with eight lines and 4 testers. Good performance combination was found between the varieties CRIS-134 and BH-147. The former was a good candidate for fibre length improvement and the latter, a good parent for yield improvement. The specific combin- ing ability suggested that both additive and dominant genes controlled the characters. Hybrid performance per se may be used to predict the parental performance for specific combining ability and thus for hybrid crop development.